The Penetration of Canon Law into the Duchy of Bohemia up to the End of the 12th Century - Krafl, Pavel (Teisė, 2023)
The subject of this article is the reception of Canon Law in the Duchy of Bohemia in the period until the end of the 12th century. The period from the beginnings of the Duchy of Bohemia to the end of the 12th century is a period in which the Duke held all the power in the State. Ecclesiastical Law was thus reduced to State Ecclesiastical Law.
Keywords: medieval Canon Law; Duchy of Bohemia; State Ecclesiastical Law; ducal statutes; archdeacon; Burchard of Worms; Ivo of Chartres